Una pedagogía por símbolos e imágenes simbólicas - Ferrer Ventosa, Roger (2018)
Freemasonry has a very unique way of spreading its ideas among the initiated of the organisation. This epistemology comes from various sources, but in all of them, the symbol, even more, the symbolic image, has a key role. A recent editorial novelty, Simbolismo masónico (Masonic symbolism), by J.J. García Arranz, studies it. In the following pages, I will try to delimit what constitutes this method of communicating ideas, especially in its visual dimension. I will elaborate on this matter with the help of this document by García Arranz, as well as the review published in REHMLAC+.